Enterprise characteristics and occupational health literacy among essential service workers in Guangdong Province, China: a cross-sectional study - Shanyu Zhou; Huiqing Chen; Junle Wu; Bing Xia; Xinyang Yu; Manqi Huang; Min Yang (Frontiers in Public Health)
BackgroundEssential service workers are exposed to significant occupational health risks. Low occupational health literacy (OHL) has been linked to increased risks of occupational injuries and work-related illnesses. However, limited evidence exists regarding the OHL of essential service workers and the impact of enterprise characteristics on OHL. This study aimed to examine the associations between enterprise characteristics and OHL among essential service workers in Guangdong Province, China.Study designCross-sectional study.MethodsA cross-sectional survey was conducted among 2,640 essential service workers from the environmental sanitation (n = 880), transportation (n = 880), and express and food delivery industries (n = 880), using multi-stage cluster random sampling. OHL was assessed using the National Occupational Health Literacy Monitoring Questionnaire, which measures four dimensions: knowledge of occupational health laws, knowledge of occupational health protection, skills of occupational health protection, and healthy work patterns and behaviors. Multivariable logistic regression was used to examine associations between enterprise characteristics (scale, ownership, industry) and OHL, with stratified analyses by monthly income.ResultsThe overall OHL level among essential service workers was 52.8%. Working in small and micro enterprises (adjusted OR = 1.42, 95% CI: 1.17–1.72) and private enterprises (adjusted OR = 1.28, 95% CI: 1.05–1.55) was associated with higher OHL, while employment in the express and food delivery industry was associated with lower OHL (adjusted OR = 0.64, 95% CI: 0.49–0.82). Monthly income significantly moderated these associations, with stronger effects observed in higher-income groups.ConclusionEnterprise characteristics significantly influence OHL among essential service workers. Targeted OHL promotion strategies should be developed based on enterprise characteristics, with particular attention to large, state-owned enterprises and express and food delivery workers.